A comparative analysis of the ontogeny of syngnathids (pipefishes and seahorses) reveals how heterochrony contributed to their diversification. Issue 5 (21st November 2022) - Schneider, Ralf F.; Woltering, Joost M.; Adriaens, Dominique; Roth, Olivia
Abstract: Background: Syngnathids are a highly derived and diverse fish clade comprising the pipefishes, pipe‐horses, and seahorses. They are characterized by a plethora of iconic traits that increasingly capture the attention of biologists, including geneticists, ecologists, and developmental biologists. The current understanding of the origins of their derived body plan is, however, hampered by incomplete and limited descriptions of the early syngnathid ontogeny. Results: We provide a comprehensive description of the development of Nerophis ophidion, Syngnathus typhle, and Hippocampus erectus from early cleavage stages to release from the male brooding organ and beyond, including juvenile development. We comparatively describe skeletogenesis with a particular focus on dermal bony plates, the snout‐like jaw morphology, and appendages. Conclusions: This most comprehensive and detailed account of syngnathid development to date suggests that convergent phenotypes (e.g., reduction and loss of the caudal fins), likely arose by distinct ontogenetic means in pipefishes and seahorses. Comparison of the ontogenetic trajectories of S. typhle and H. erectus provides indications that characteristic features of the seahorse body plan result from developmental truncation. Altogether, this work provides a valuable resource and framework for future research to understand the evolution of the outlandish syngnathid morphology from a developmental perspective. Key Findings: This study provides a comprehensive description of syngnathid (pipefishes & seahorses) development and skeletogenesis, highlighting how and when iconic features arise during the early ontogeny and across representatives of three main clades of this fish family. By comparatively analyzing the development of skeletal elements contributing to many of these fishes' most iconic features, such as their snout‐like facial morphology, the absence of certain fins and the bony plate armor, we identify key stages, structures, and suggest evolutionary mechanisms driving their unique ontogenetic trajectories. We find that several iconic syngnathid traits are the result of developmental truncation, leading to neotenic features or even feature loss, and we conclude that developmental heterochrony likely played a central role in establishing the diversity found among many morphological traits across and within syngnathid species.